SISTEM INFORMASI AKADEMIK PADA SMK YAYASAN PEMBANGUNAN PENDIDIKAN BEKASI - Ira Sri Kusuma; Siti Nurbaya Ambo; Linda Sari Dewi (Jurnal Sistem Informasi, 2014)
ABSTRACT— Advances in technology today is mainly based on the Internet is very helpful in providing information quickly and easily. Many found from schools that do not use the internet to provide information about the school such as new student enrollment, academic value information, and activities that exist in school. SMK YPP (Yayasan Pembangunan Pendidikan) Bekasi is one of the schools that do not have a system of information via the internet and feels is in need of a web-based information system in order to provide better convenience for teachers, students, and the community. In designing a web based academic system used waterfall method, the use of this information system provides easy access to information, values, and activities that will take place, besides the author using the program tools UML (Unified Modeling Language) for smooth understanding. Keywords: Information Systems, waterfall, UML.